HUMAN RESOURCES DEVELOPMENT OF UMKM AND CREATIVE ECONOMY ACTORS IN PADANG PARIAMAN REGENCY - Arief, Diana Ross; Sari, Galuh Puspita Sari Puspita; Saputra, Andri; Yuafni, Yuafni (Universitas Negeri Makassar, 2024)
Padang Pariaman Regency not only has the potential for tourist destinations, but also produces handicrafts such as: pandan weaving, Kapalo Paniti Nareh embroidery, and batik. However, the ability of MSMEs in processing crafts in various products is limited. This study aims to foster human resources of Padang Pariaman MSMEs in developing the potential of woven pandan duri crafts, batik and Kapalo Paniti Nareh embroidery that can contribute to economic growth. The training in the form of a workshop was held for five days in collaboration with the Industrial Business Incubator (IBI) and the Research and Community Service Unit of the ATK Yogyakarta Polytechnic (UPPM) together with the Padang Pariaman Regency Government. Through the training, three participants consisting of embroidery crafts, clothing and leather products in the form of bags and wallets, were able to make tote bags and clutches made of leather with a combination of pandan weaving and batik cloth and embroidery. The results of the evaluation in the form of observations, interviews, pre-tests/post-tests, questionnaires, and documentation, related to the speakers, coordination, quality of facilities & infrastructure, consumption of training expectations, and benefits of training showed that the average participant satisfaction score was 93.3%.